The Influence of Transformational Leadership Style on Employee Performance with Organizational Citizenship Behavior as a Moderator Variable in PD. BPR KALSEL - Rasyid, Muhammad Zakiyyul Fuad; Al Faridho Awwal, Muhammad; Nashoha, Muhammad Rizalun; Hermawan, Hengki Dwiyan (IJBLE Scientific Publications Community Inc., 2025)
The objectives of research are to describe transformational leadership style, employee performance, and organizational citizenship behavior (OCB), and to examine the influence of transformational leadership style on employee performance through organizational citizenship behavior (OCB) as moderator variable. Sampling technique is stratified sampling. The respondent of research is 77 persons. The analysis tool is Partial Least Square (PLS). Research respondent is the employee of PD. BPR of South Kalimantan. Result of research indicates that transformational leadership style and employee performance remain in high category. Transformational leadership style has significant direct influence on employee performance. Organizational citizenship behavior (OCB) belongs to high category. The moderating nature of organizational citizenship behavior (OCB) is moderating of strengthening which means that higher organizational citizenship behavior (OCB) will empower the influence of transformational leadership style on employee performance.